2021
DOI: 10.3389/fpsyg.2020.612241
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Outcomes in Healthcare Workers in COVID-19 and Non-COVID-19 Care Units: A Cross-Sectional Survey in Belgium

Abstract: BackgroundThe literature shows the negative psychological impact of the coronavirus disease 2019 (COVID-19) outbreak on frontline healthcare workers. However, few are known about the mental health of physicians and nurses working in general hospitals during the outbreak, caring for patients with COVID-19 or not.ObjectivesThis survey assessed differences in mental health in physicians and nurses working in COVID-19 or non-COVID-19 medical care units.DesignA cross-sectional mixed-mode survey was used to assess b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
103
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(147 citation statements)
references
References 28 publications
16
103
1
1
Order By: Relevance
“…Likewise, another study from Italy, involving 1,153 HCWs showed that those who were directly involved with COVID-19 patients experienced higher levels of burnout and associated somatic symptoms (such as muscle tension, sleep problems and changes in eating) [ 76 ]. Other studies however failed to confirm these differences including this study from Belgium in 647 HCWs were higher level of burnout, insomnia, and anxiety were noted among nurses in comparison to physicians but not in HCWs working in Covid-19 care units compared to those working in non-Covid-19 care units or in both [ 86 ]. Similarly, in a study from Romania first-line trainees (e.g.…”
Section: Burnout and Resiliencementioning
confidence: 76%
“…Likewise, another study from Italy, involving 1,153 HCWs showed that those who were directly involved with COVID-19 patients experienced higher levels of burnout and associated somatic symptoms (such as muscle tension, sleep problems and changes in eating) [ 76 ]. Other studies however failed to confirm these differences including this study from Belgium in 647 HCWs were higher level of burnout, insomnia, and anxiety were noted among nurses in comparison to physicians but not in HCWs working in Covid-19 care units compared to those working in non-Covid-19 care units or in both [ 86 ]. Similarly, in a study from Romania first-line trainees (e.g.…”
Section: Burnout and Resiliencementioning
confidence: 76%
“…Furthermore, in our review, general and frontline staff recorded similar levels of psychological distress. Several previous studies demonstrated a higher psychological impact for frontline staff, yet others showed that the mental health effects of the crisis were equally felt across settings or specialties [58-60].…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to the aforementioned conditions, it is still unclear how the COVID-19 pandemic has affected the burnout prevalence amongst HCW. Included studies suggest a significant increase in burnout prevalence in HCW, comparable to those found for depression, anxiety, PTSD and stress, with values up to 45.6% [ 12 ▪ ]. The extended duration of the pandemic will likely lead to an even more increased burnout prevalence in the coming months.…”
Section: Burnoutmentioning
confidence: 99%
“…The impact of the COVID-19 pandemic on sleep disturbances in nurses and medical doctors was only assessed in two studies [ 12 ▪ , 13 ]. Here, both studies showed that sleep disturbances were frequent in HCW (prevalence rates up to 68.7%) and both showed that these were more frequent in nurses; thus, being in line with the aforementioned findings of more affective and stress-related disorders in nurses.…”
Section: Other Mental Health Aspectsmentioning
confidence: 99%
See 1 more Smart Citation